UV curing coating with electromagnetic shielding effect and preparation method thereof

By wrapping ferromagnetic particles with homemade magnetic core-shell rubber particles, a UV cured coating with electromagnetic shielding and impact resistance is formed, solving the problems of agglomeration, settlement and insufficient toughness of existing materials during use.

CN119799048APending Publication Date: 2025-04-11YANTAI DARBOND TECH
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411966354.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-30
Publication Date
2025-04-11

AI Technical Summary

Technical Problem

The existing iron tetroxide materials are prone to agglomeration and settlement during use, and cannot improve the toughness and impact resistance of the material, and cannot meet the needs of polymer materials in electromagnetic shielding and impact resistance.

Method used

The self-made magnetic core-shell rubber particles are used to encase the ferromagnetic particles in the core-shell structure through emulsification and grafting process to form a UV cured coating with electromagnetic shielding effect.

Benefits of technology

The UV cured coating has excellent impact strength while achieving electromagnetic shielding performance, avoiding the problem of settlement and agglomeration of materials during use or storage.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention belongs to the technical field of high polymer material preparation, and particularly relates to a UV curing coating with an electromagnetic shielding effect and a preparation method of the UV curing coating with the electromagnetic shielding effect. The invention relates to a light-sensitive ink which comprises the following components in parts by weight: 20-50 parts of a monofunctional diluent, 10-30 parts of a bifunctional diluent, 10-30 parts of toughened resin, 3-10 parts of a photoinitiator, 0.5-2 parts of a blue pigment and 10-30 parts of self-made magnetic core-shell rubber particles. The UV curing coating with the electromagnetic shielding effect prepared by the invention not only has the advantages of high photocuring speed, high efficiency and the like of a conventional UV curing coating, but also has excellent impact strength while having the electromagnetic shielding effect due to the adoption of the self-made magnetic core-shell rubber particles after being cured; and meanwhile, the UV curing coating has relatively good storage stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of polymer material preparation, and in particular relates to a UV curing coating with electromagnetic shielding function and a preparation method thereof. Background Art

[0002] With the rapid popularization of contemporary 5G electronic information technology, electromagnetic pollution and electromagnetic interference caused by electromagnetic wave radiation in the civilian field have gradually attracted people's attention; in the field of national defense construction, certain magnetic materials can absorb or greatly reduce the electromagnetic wave energy projected onto its surface, reduce electromagnetic wave interference, and can reduce the impact of radar, infrared and other detection systems on targets as much as possible, and improve the survivability of aircraft. The above fields will use absorbing coating materials, which require the materials to have the characteristics of high toughness and high impact strength. Ferroferric oxide has superparamagnetism and is a good magnetic absorbing material, but the unmodified ferroferric oxide often encounters problems such as easy agglomeration and sedimentation during use, and cannot improve the toughness and impact resistance of the material. Summary of the invention

[0003] In view of the deficiencies of the prior art, the present invention provides a UV curing coating with electromagnetic shielding function and a preparation method thereof.

[0004] To achieve the above objectives, the technical solutions adopted are:

[0005] One of the purposes of the present invention is to provide a UV curing coating with electromagnetic shielding effect, which comprises, by weight: 20 to 50 parts of monofunctional diluent, 10 to 30 parts of difunctional diluent, 10 to 30 parts of toughening resin, 3 to 10 parts of photoinitiator, 0.5 to 2 parts of blue pigment, and 10 to 30 parts of self-made magnetic core-shell rubber particles.

[0006] Furthermore, the method for preparing the self-made magnetic core-shell rubber particles comprises the following steps:

[0007] (1) Prepare FeCl using deionized water 2 With FeCl 3 The aqueous solution of is used as the aqueous phase W11, the aqueous solution of NaOH and the reducing agent is prepared with deionized water as the aqueous phase W12, and the rubber latex is prepared with chloroform and dichloromethane as the oil phase O1; the aqueous phase W11 is mixed with the oil phase O1, and the emulsifier E1 is added, and the rotation speed, temperature and time are controlled to prepare the colostrum emulsion W11 / O1; the aqueous phase W12 is mixed with the oil phase O1, and the emulsifier E1 is added, and the rotation speed, temperature and time are controlled to prepare the colostrum emulsion W12 / O1;

[0008] (2) Add the colostrum emulsion W11 / O1 and colostrum emulsion W12 / O1 into deionized water in which the emulsifier E2 is dispersed in advance, and heat the reaction to obtain the magnetic particles Fe coated therein. 3 O 4 of latex particles;

[0009] (3) wrapping the magnetic particles Fe in step (2) 3 O 4 The prepared grafted acrylic ester monomer mixture oil phase O2 is added to the latex particle bundle, and the reaction temperature is controlled. 3 O 4 The outer layer of the latex particle beam is grafted with an acrylate monomer; wherein the preparation process of the oil phase O2 comprises the following steps: dissolving the acrylate monomer and the initiator in a mixed solution of chloroform and dichloromethane;

[0010] (4) The temperature is raised to 60-100° C., and the chloroform and dichloromethane solvents are removed by condensation and reflux, and the product is filtered, washed and dried to obtain the final product.

[0011] Further, in step (1), FeCl 2 、FeCl 3 The mass ratios of NaOH, deionized water and reducing agent in the water phase W12 are 27-45:13-15:40-60 respectively; the mass ratios of chloroform, dichloromethane and rubber latex in the oil phase O1 are 23-60:30-47:10-30 respectively; the mass ratios of water phase W11, oil phase O1 and emulsifier E1 are 10-40:55-89:1-5 respectively; the mass ratios of water phase W12, oil phase O1 and emulsifier E1 are 10-45:50-89:1-5 respectively.

[0012] The beneficial effect of adopting the above technical solution is that the role of emulsifier E1 is to make W11 and W12 stably exist in O1 and O2, and the purpose of selecting chloroform and dichloromethane for oil phase O1 is to adjust the stability of oil phase O1 in W2 according to the difference in density extractability between the two.

[0013] Furthermore, the reducing agent is at least one of N,N-dimethyl-p-toluidine, tetramethylthiourea, and aldehyde-amine condensation products; the rubber latex is at least one of natural rubber latex, epoxidized natural rubber latex, nitrile rubber latex, and acrylate emulsion; and the emulsifier E1 is at least one of sucrose fatty acid ester, polyglycerol fatty acid ester, and polyoxyethylene castor oil.

[0014] The beneficial effect of adopting the above technical solution is that the reducing agent promotes the decomposition of the initiator to generate free radicals, which trigger the grafting of acrylate monomers around the latex particles that wrap the magnetic particles.

[0015] Furthermore, in step (1), the stirring speed is 500 to 1000 rpm / min, the temperature is 20 to 30° C., and the time is 10 to 30 min.

[0016] Furthermore, the step (2) further comprises the following steps: mixing deionized water and emulsifier E2 in advance at a stirring speed of 500 to 1000 rpm / min, a temperature of 20 to 30° C., and a time of 10 to 30 min, wherein the mass ratio of deionized water to emulsifier E2 is 95-99:1-5, and is recorded as W2; the mass ratios of W11 / O1, W12 / O1, and W2 are 10-20:10-20:60-80 respectively; and the emulsifier E2 is at least one of glyceryl stearate PEG-100, Croda A165 emulsifier, ABIL CARE 85 silicone emulsifier, EG emulsifier, Prexin 721 emulsifier, and BASF A25 emulsifier.

[0017] The beneficial effect of adopting the above technical solution is that the role of the emulsifier E2 is to make W11 / O1 and W12 / O1 stably exist in W2, prevent W11 and W12 from demulsifying in O1 and O2 respectively, and at the same time, adjusting the ratio of (W11 / O1) and (W12 / O1) can regulate the magnetic Fe in the latex particles. 3 O 4 Particle content.

[0018] Furthermore, the temperature of the temperature-raising reaction in step (2) is 40 to 70° C., and the reaction time is 10 to 90 minutes.

[0019] Furthermore, the step (3) further comprises the following steps: mixing chloroform, dichloromethane, acrylate monomer and initiator in advance at a stirring speed of 500 to 1000 rpm / min, a temperature of 20 to 30° C. and a time of 10 to 30 min, and recording the mixture as oil phase O2, wherein the mass ratios of chloroform, dichloromethane, acrylate monomer and initiator in the oil phase O2 are 14-25:26-49:25-55:1-5 respectively; dropping the mixed oil phase O2 onto the Fe2O3 coated magnetic particles while stirring. 3 O 4 The stirring speed is 500-1000 rpm / min, and the magnetic particles Fe are wrapped in the latex particle beam. 3 O 4 The material temperature of the latex particle beam is 30-60°C.

[0020] Furthermore, the mass ratio of the sum of the three W11 / O1, W12 / O1, and W2 to the oil phase O2 is 60-80:20-40; the acrylate monomer is at least one of styrene St, acrylonitrile AN, and methyl methacrylate MMA, and the initiator is at least one of benzoyl peroxide and isopropylbenzene hydroperoxide.

[0021] The beneficial effect of adopting the above technical solution is that the purpose of this step of reaction is to wrap the magnetic particles Fe 3 O 4 The outer layer of the latex particle bundle is grafted with acrylic acid ester monomer. In this step, chloroform and dichloromethane are used as the oil phase O2 in order to adjust the stability of the oil phase O2 in W2 according to the difference in density and extractability between the two.

[0022] Furthermore, the cleaning in step (4) is to first use anhydrous ethanol to wash the product 1 to 2 times, and then use deionized water to wash 3 to 4 times, and the drying is to dry at 80° C. for 2 hours.

[0023] The beneficial effect of adopting the above technical solution is that the purpose of using anhydrous ethanol for washing is to wash away the excess unreacted acrylate monomer in step (3).

[0024] Furthermore, the monofunctional diluent is at least one of isobornyl acrylate, glyceryl acetonide acrylate, benzyl acrylate, hydroxyethyl acrylate, and hydroxypropyl acrylate; the difunctional diluent is at least one of 1,6-hexanediol diacrylate, dipropylene glycol diacrylate, and ethoxylated bisphenol A diacrylate; the toughening resin is at least one of CN8004, CN3108, and CN704 produced by Sartomer; the photoinitiator is at least one of 1-hydroxycyclohexyl phenyl ketone, 2,4,6-trimethylbenzoyl diphenylphosphine, and benzoin dimethyl ether; the blue pigment is at least one of Runba P5040LW, BASF L7101F, and BASF 7080K.

[0025] The second purpose of the present invention is to provide a method for preparing a UV-curing coating with electromagnetic shielding effect, comprising the following steps: adding a monofunctional diluent, a difunctional diluent, a photoinitiator, and a blue pigment according to their weight proportions and stirring for 1 to 2 hours at a stirring speed of 800 to 1200 r / min, until the material becomes uniform and fine; then adding homemade magnetic core-shell rubber particles and stirring for 1 to 2 hours at a stirring speed of 500 to 1000 r / min, until the material becomes uniform and fine; finally adding a toughening resin and stirring for 0.5 to 1 hour at a stirring speed of 800 to 1200 r / min; during the whole process, the material temperature is controlled at 20 to 30°C; finally, vacuuming for 5 minutes to degas, discharge, and seal and package the material; the vacuum degree is ≤-0.095Mpa.

[0026] Compared with the prior art, the present invention has the following beneficial effects:

[0027] The invention prepares a UV-curing coating with electromagnetic shielding effect, adopts self-synthesized core-shell rubber particles, and the core-shell rubber structure can stably wrap ferroferric oxide magnetic particles during the emulsification grafting process, so that the final UV-curing coating has electromagnetic shielding performance and excellent impact strength, and has excellent stability during use and storage, and will not have problems such as sedimentation and agglomeration. DETAILED DESCRIPTION

[0028] The principles and features of the present invention are described below. The examples given are only used to explain the present invention and are not used to limit the scope of the present invention.

[0029] Blank group experiment:

[0030] Add 38.5 parts of isobornyl acrylate, 15 parts of 1,6-hexanediol diacrylate, 2 parts of 1-hydroxycyclohexyl phenyl ketone, 3 parts of 2,4,6-trimethylbenzoyl diphenoxyphosphine, and 1.5 parts of Runba P5040LW according to weight parts, and stir for 1.5 hours at a stirring speed of 1000 r / min. The material becomes uniform and fine. Finally, add 20 parts of Sartomer CN8004 resin and stir for 1 hour at a stirring speed of 1000 r / min. The material temperature is controlled at 25°C during the whole process. Finally, vacuumize for 5 minutes to degas, discharge and seal the material, and the vacuum degree is ≤-0.095Mpa.

[0031] Example 1

[0032] Add 38.5 parts of isobornyl acrylate, 15 parts of 1,6-hexanediol diacrylate, 2 parts of 1-hydroxycyclohexyl phenyl ketone, 3 parts of 2,4,6-trimethylbenzoyl diphenoxyphosphine, and 1.5 parts of Runba P5040LW according to weight parts, stir for 1.5 hours at a stirring speed of 1000r / min, and the material becomes uniform and fine. Then add 20 parts of homemade magnetic core-shell rubber particles, stir for 1.5 hours at a stirring speed of 800r / min, and the material becomes uniform and fine. Finally, add 20 parts of Sartomer CN8004 resin, stir for 1 hour at a stirring speed of 1000r / min. The material temperature is controlled at 25°C during the whole process. Finally, vacuum for 5 minutes to degas, discharge, seal and package, and the vacuum degree is ≤-0.095Mpa;

[0033] The preparation process of homemade magnetic core-shell rubber particles is as follows:

[0034] The first step is to weigh FeCl 2 :25.2g, FeCl 3: 12.6g, deionized water: 52.2g, according to the speed of 600rpm / min, the temperature is 25℃, stirred for 15min, recorded as water phase W11 for standby; weigh NaOH: 22.4g, deionized water: 69.5g, N, N-dimethyl-p-toluidine 0.82g, according to the speed of 600rpm / min, the temperature is 25℃, stirred for 15min, recorded as water phase W12 for standby; weigh chloroform: 200g, dichloromethane: 400g, natural rubber latex: 200g, according to the speed of 600 rpm / min, the temperature is 25℃, stir for 15min, record it as oil phase O1 for later use; weigh water phase W11: 85g, oil phase O1: 490g, sucrose fatty acid ester: 12g, according to the speed of 600rpm / min, the temperature of 25℃, stir for 15min, record it as W11 / O1 for later use; weigh water phase W12: 100g, oil phase O1: 480g, polyglycerol fatty acid ester: 12g, according to the speed of 600rpm / min, the temperature of 25℃, stir for 15min, record it as W12 / O1 for later use;

[0035] In the second step, deionized water: 3590g, glyceryl stearate PEG-100: 108g were weighed, and the mixture was stirred at a speed of 600rpm / min and a temperature of 25°C for 15min, which was recorded as W2 for later use; (W11 / O1): 580g, (W12 / O1): 580g, W2: 2000g were weighed, and the mixture was stirred at a speed of 800rpm / min and a temperature of 50°C for 20min to obtain a product of Fe coated magnetic particles. 3 O 4 of latex particles;

[0036] The third step is to weigh 200 g of chloroform, 400 g of dichloromethane, 360 g of styrene St, and 36 g of benzoyl peroxide, stir at a speed of 600 rpm / min and a temperature of 25°C for 15 min, and record it as oil phase O2 for later use; take 900 g of oil phase O2 and add it dropwise to the product of the second step while stirring, at a stirring speed of 800 rpm / min, and the material temperature during the addition is 45°C. The product of this step is the magnetic particle Fe wrapped in the 3 O 4 The outer layer of the latex particle bundle is grafted with an acrylate monomer;

[0037] In the fourth step, the product of the third step is heated to 80°C and condensed under reflux to remove chloroform and dichloromethane solvents, and then the above product is filtered and washed twice with anhydrous ethanol and then washed three times with deionized water, and then dried at 80°C for 2h to obtain the self-made magnetic core-shell rubber particles.

[0038] Example 2

[0039] Add 30 parts of acetone glycerol acrylate, 8.5 parts of hydroxyethyl acrylate, 15 parts of dipropylene glycol diacrylate, 2.5 parts of benzoin dimethyl ether, 2.5 parts of 2,4,6-trimethylbenzoyl diphenoxyphosphine, and 1.5 parts of BASF L7101F according to weight parts, stir for 1.5 hours at a stirring speed of 1000r / min, and the material becomes uniform and fine. Then add 20 parts of homemade magnetic core-shell rubber particles, stir for 1.5 hours at a stirring speed of 800r / min, and the material becomes uniform and fine. Finally, add 20 parts of Sartomer CN3108 resin, stir for 1 hour at a stirring speed of 1000r / min. The material temperature is controlled at 25°C during the whole process. Finally, vacuum for 5 minutes to degas, discharge, seal and package, and the vacuum degree is ≤-0.095Mpa;

[0040] The preparation process of homemade magnetic core-shell rubber particles is as follows:

[0041] The first step is to weigh FeCl 2 :25.8g, FeCl 3 : 12.0g, deionized water: 52.2g, according to the speed of 600rpm / min, the temperature is 25℃, stirred for 15min, recorded as water phase W11 for standby; weigh NaOH: 23.9g, deionized water: 68g, tetramethylthiourea 2.2g, according to the speed of 600rpm / min, the temperature is 25℃, stirred for 15min, recorded as water phase W12 for standby; weigh chloroform: 400g, dichloromethane: 400g, nitrile rubber emulsion: 200g, according to the speed of 600rpm / m in, the temperature is 25°C, stirred for 15 minutes, recorded as oil phase O1 for later use; weigh water phase W11: 80g, oil phase O1: 485g, polyglycerol fatty acid ester: 12g, according to the speed of 600rpm / min, the temperature of 25°C, stirred for 15min, recorded as W11 / O1 for later use; weigh water phase W12: 100g, oil phase O1: 480g, polyglycerol fatty acid ester: 12g, according to the speed of 600rpm / min, the temperature of 25°C, stirred for 15min, recorded as W12 / O1 for later use;

[0042] In the second step, weigh deionized water: 3590g, Prexin 721 emulsifier: 108g, stir at a speed of 600rpm / min, temperature of 25°C for 15min, record as W2 for standby; weigh (W11 / O1): 580g, (W12 / O1): 580g, W2: 2000g, stir at a speed of 800rpm / min, temperature of 50°C for 20min, and obtain the product of magnetic particle Fe coated 3 O 4 of latex particles;

[0043] The third step is to weigh 200g of chloroform, 400g of dichloromethane, 360g of acrylonitrile AN, and 36g of isopropylbenzene hydroperoxide, stir at a speed of 600rpm / min and a temperature of 25°C for 15min, and record it as oil phase O2 for later use; take 900g of oil phase O2 and add it dropwise to the product of the second step while stirring, at a stirring speed of 800rpm / min, and the material temperature during the addition is 45°C. The product of this step is the outer layer of the latex particle bundle wrapping the magnetic particle Fe3O4 grafted with an acrylate monomer;

[0044] In the fourth step, the product of the third step is heated to 80°C and condensed under reflux to remove chloroform and dichloromethane solvents, and then the above product is filtered and washed twice with anhydrous ethanol and then washed three times with deionized water, and then dried at 80°C for 2h to obtain the self-made magnetic core-shell rubber particles.

[0045] Example 3

[0046] Add 26.5 parts of benzyl acrylate, 7 parts of hydroxypropyl acrylate, 15 parts of ethoxylated bisphenol A diacrylate, 1 part of 1-hydroxycyclohexyl benzophenone, 1.5 parts of benzoin dimethyl ether, 2.5 parts of 2,4,6-trimethylbenzoyl diphenoxyphosphine, and 1.5 parts of BASF 7080K according to weight parts, stir for 1.5 hours at a stirring speed of 1000r / min, and the material becomes uniform and fine. Then add 25 parts of homemade magnetic core-shell rubber particles, stir for 1.5 hours at a stirring speed of 800r / min, and the material becomes uniform and fine. Finally, add 20 parts of Sartomer CN704 resin, stir for 1 hour at a stirring speed of 1000r / min. The material temperature is controlled at 25°C during the whole process. Finally, vacuum for 5 minutes to degas, discharge, seal and package, and the vacuum degree is ≤-0.095Mpa;

[0047] The preparation process of homemade magnetic core-shell rubber particles is as follows:

[0048] The first step is to weigh FeCl 2 :24g, FeCl 3: 13.8g, deionized water: 52.2g, according to the speed of 600rpm / min, the temperature is 25℃, stirred for 15min, recorded as water phase W11 for standby; weigh NaOH: 23g, deionized water: 68.9g, N, N-dimethyl-p-toluidine 0.82g, according to the speed of 600rpm / min, the temperature is 25℃, stirred for 15min, recorded as water phase W12 for standby; weigh chloroform: 450g, dichloromethane: 350g, acrylate emulsion: 200g, according to the speed of 600rp m / min, the temperature is 25°C, stirred for 15 minutes, recorded as oil phase O1 for later use; weigh water phase W11: 85g, oil phase O1: 490g, polyoxyethylene castor oil: 12g, according to the speed of 600rpm / min, the temperature of 25°C, stirred for 15min, recorded as W11 / O1 for later use; weigh water phase W12: 100g, oil phase O1: 480g, polyglycerol fatty acid ester: 12g, according to the speed of 600rpm / min, the temperature of 25°C, stirred for 15min, recorded as W12 / O1 for later use;

[0049] In the second step, weigh deionized water: 3590g, BASF A25 emulsifier: 108g, stir at a speed of 600rpm / min, temperature of 25℃ for 15min, record as W2 for standby; weigh (W11 / O1): 580g, (W12 / O1): 580g, W2: 2000g, stir at a speed of 800rpm / min, temperature of 50℃ for 20min, and obtain the product of magnetic particle Fe coated 3 O 4 of latex particles;

[0050] The third step is to weigh 550 g of chloroform, 250 g of dichloromethane, 360 g of methyl methacrylate (MMA), and 36 g of benzoyl peroxide, and stir them at a speed of 600 rpm / min and a temperature of 25°C for 15 min, which is recorded as oil phase O2 for later use; 900 g of oil phase O2 is added dropwise to the product of the second step while stirring, at a stirring speed of 800 rpm / min, and the material temperature during the addition is 45°C. The product of this step is the magnetic particles Fe coated with 3 O 4 The outer layer of the latex particle bundle is grafted with an acrylate monomer;

[0051] In the fourth step, the product of the third step is heated to 80°C and condensed under reflux to remove chloroform and dichloromethane solvents, and then the above product is filtered and washed twice with anhydrous ethanol and then washed three times with deionized water, and then dried at 80°C for 2h to obtain the self-made magnetic core-shell rubber particles.

[0052] Comparative Example 1

[0053] Add 26.5 parts of benzyl acrylate, 7 parts of hydroxypropyl acrylate, 15 parts of ethoxylated bisphenol A diacrylate, 1 part of 1-hydroxycyclohexyl benzophenone, 1.5 parts of benzoin dimethyl ether, 2.5 parts of 2,4,6-trimethylbenzoyl diphenoxyphosphine, and 1.5 parts of BASF 7080K according to weight parts, stir for 1.5 hours at a stirring speed of 1000r / min, and the material becomes uniform and fine. Then add 25 parts of homemade inorganic particles, stir for 1.5 hours at a stirring speed of 800r / min, and the material becomes uniform and fine. Finally, add 20 parts of Sartomer CN704 resin, stir for 1 hour at a stirring speed of 1000r / min. The material temperature is controlled at 25°C during the whole process. Finally, vacuum for 5 minutes to degas, discharge, seal and package, and the vacuum degree is ≤-0.095Mpa;

[0054] The preparation process of homemade inorganic particles is as follows:

[0055] The first step is to weigh FeCl 2 :26g、FeCl 3 : 15.2g, deionized water: 62g, according to the speed of 600rpm / min, the temperature is 25℃, stir for 15min, record it as water phase W11 for standby; weigh NaOH: 26g, deionized water: 68.9g, according to the speed of 600rpm / min, the temperature is 25℃, stir for 15min, record it as water phase W12 for standby; weigh chloroform: 200g, dichloromethane: 400g, according to the speed of 600rpm / min, the temperature is 25℃, stir 15min, recorded as oil phase O1 for later use; weigh water phase W11: 85g, oil phase O1: 490g, polyoxyethylene castor oil: 12g, according to the speed of 600rpm / min, the temperature of 25℃, stir for 15min, recorded as W11 / O1 for later use; weigh water phase W12: 100g, oil phase O1: 480g, polyglycerol fatty acid ester: 12g, according to the speed of 600rpm / min, the temperature of 25℃, stir for 15min, recorded as W12 / O1 for later use;

[0056] In the second step, weigh deionized water: 3590g, BASF A25 emulsifier: 120g, according to the speed of 600rpm / min, the temperature of 25℃, stir for 15min, record as W2 for standby; weigh (W11 / O1): 580g, (W12 / O1): 580g, W2: 2000g, according to the speed of 800rpm / min, the temperature of 50℃, stir for 20min, and obtain the product of magnetic particle Fe wrapped 3 O 4 of latex particles;

[0057] In the third step, the product of the second step is heated to 80°C, condensed and refluxed to remove chloroform and dichloromethane solvents, and then the above product is filtered, and the product is first washed twice with anhydrous ethanol, and then washed three times with deionized water, and then dried at 80°C for 2h to obtain the final product.

[0058] Comparative Example 2

[0059] Add 26.5 parts of benzyl acrylate, 7 parts of hydroxypropyl acrylate, 15 parts of ethoxylated bisphenol A diacrylate, 1 part of 1-hydroxycyclohexyl benzophenone, 1.5 parts of benzoin dimethyl ether, 2.5 parts of 2,4,6-trimethylbenzoyl diphenoxyphosphine, and 1.5 parts of BASF 7080K according to weight parts, stir for 1.5 hours at a stirring speed of 1000r / min, and the material becomes uniform and fine. Then add 25 parts of homemade core-shell rubber particles, stir for 1.5 hours at a stirring speed of 800r / min, and the material becomes uniform and fine. Finally, add 20 parts of Sartomer CN704 resin, stir for 1 hour at a stirring speed of 1000r / min. The material temperature is controlled at 25°C during the whole process. Finally, vacuum for 5 minutes to degas, discharge, seal and package, and the vacuum degree is ≤-0.095Mpa;

[0060] The preparation process of homemade core-shell rubber particles is as follows:

[0061] The first step is to weigh deionized water: 75g, N, N-dimethyl-p-toluidine 1.0g, according to the speed of 600rpm / min, the temperature of 25°C, stir for 15min, record as W1 for standby; weigh chloroform: 450g, dichloromethane: 350g, acrylate emulsion: 250g, according to the speed of 600rpm / min, the temperature of 25°C, stir for 15min, record as oil phase O1 for standby; weigh W1: 90g, oil phase O1: 500g, polyoxyethylene castor oil: 12g, according to the speed of 600rpm / min, the temperature of 25°C, stir for 15min, record as W1 / oil phase O1 for standby;

[0062] The second step is to weigh 3590g of deionized water and 120g of BASF A25 emulsifier, stir at a speed of 600rpm / min and a temperature of 25°C for 15min, and record it as W2 for standby; weigh 600g of W1 / oil phase O1 and 3600g of W2, stir at a speed of 800rpm / min and a temperature of 50°C for 20min, and obtain a latex particle bundle encapsulating a reducing agent;

[0063] The third step is to weigh 200g of chloroform, 400g of dichloromethane, 360g of methyl methacrylate MMA, and 36g of benzoyl peroxide, stir at a speed of 600rpm / min and a temperature of 25°C for 15min, and record it as oil phase O2 for standby use; take 900g of oil phase O2 and drop it into the product of the second step while stirring, the stirring speed is 800rpm / min, and the material temperature during dropwise addition is 45°C. The product of this step is the outer layer grafted acrylate monomer of the latex particle bundle;

[0064] In the fourth step, the product of the third step is heated to 80°C, condensed and refluxed to remove chloroform and dichloromethane solvents, and then the above product is filtered, and the product is first washed twice with anhydrous ethanol, and then washed three times with deionized water, and then dried at 80°C for 2h to obtain the final product.

[0065] Specific test verification plan:

[0066] Verification scheme 1: After curing on laser treated aluminum sheet (100-120um thickness, curing conditions 365nm wavelength / 5000mj), test the falling ball impact performance, refer to GB / T1732-1993 standard;

[0067] Verification scheme 2: Electromagnetic shielding effectiveness verification, according to the standard GB / T 30140-2013, the electromagnetic shielding performance of the cured coating is tested using a fabric electromagnetic radiation protection performance tester, and the results are characterized by shielding effectiveness (SE), the unit of which is decibel (dB). The larger the SE value, the better the shielding effect.

[0068] The experimental verification data comparison is shown in Table 1:

[0069] Table 1.

[0070] Experiment No. Drop ball impact performance(J) Electromagnetic shielding effectiveness (dB) Blank Group 5J, cracking <15 Comparison group 1 5J, cracking 46 Comparison group 2 15J, no cracking ≤15 Experimental Group 1 15J, no cracking 45 Experimental Group 2 15J, no cracking 43 Experimental Group 3 15J, no cracking 46

[0071] As can be seen from the above table, the blank group has poor impact resistance and no electromagnetic shielding effectiveness; Comparative Example 1 has only good electromagnetic shielding effectiveness, but poor toughness and poor impact resistance; Comparative Example 2 has good impact resistance, but poor electromagnetic shielding effectiveness. The core-shell rubber particles with magnetic function prepared by the present invention can not only improve the impact strength of the material, but also have good electromagnetic shielding performance; different from the physical blending of conventional magnetic materials and polymer resins, the inorganic magnetic particles in the present invention are rubber core-shell structures that are wrapped and formed during the emulsification grafting process, avoiding many problems such as uneven dispersion and stratified sedimentation during later use or storage.

[0072] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.

Claims

1. A UV-curable coating with electromagnetic shielding effect, characterized in that: The invention comprises, by weight: 20 to 50 parts of monofunctional diluent, 10 to 30 parts of difunctional diluent, 10 to 30 parts of toughening resin, 3 to 10 parts of photoinitiator, 0.5 to 2 parts of blue pigment and 10 to 30 parts of self-made magnetic core-shell rubber particles.

2. The UV-curable coating with electromagnetic shielding function according to claim 1, characterized in that: The method for preparing the self-made magnetic core-shell rubber particles comprises the following steps: (1) using deionized water to prepare an aqueous solution of FeCl2 and FeCl3 as an aqueous phase W11, using deionized water to prepare an aqueous solution of NaOH and a reducing agent as an aqueous phase W12, and using chloroform and dichloromethane to prepare a rubber latex as an oil phase O1; mixing the aqueous phase W11 with the oil phase O1, adding an emulsifier E1, controlling the rotation speed, temperature and time, to prepare a colostrum emulsion W11 / O1; mixing the aqueous phase W12 with the oil phase O1, adding an emulsifier E1, controlling the rotation speed, temperature and time, to prepare a colostrum emulsion W12 / O1; (2) adding the colostrum emulsion W11 / O1 and the colostrum emulsion W12 / O1 into deionized water in which the emulsifier E2 is dispersed in advance, and heating the water to react, thereby obtaining a latex particle bundle wrapping the magnetic particle Fe3O4; (3) adding the pre-prepared grafted acrylate monomer mixture oil phase O2 to the latex particle bundle wrapping the magnetic particle Fe3O4 in step (2), controlling the reaction temperature, and grafting acrylate monomers on the outer layer of the latex particle bundle wrapping the magnetic particle Fe3O4; wherein the preparation process of the oil phase O2 includes the following steps: dissolving the acrylate monomer and the initiator in a mixed solution of chloroform and dichloromethane; (4) The temperature is raised to 60-100° C., and the chloroform and dichloromethane solvents are removed by condensation and reflux, and the product is filtered, washed and dried to obtain the final product.

3. The UV-curable coating with electromagnetic shielding function according to claim 2, characterized in that: In the step (1), the mass ratios of FeCl2, FeCl3 and deionized water in the aqueous phase W11 are 27-45:13-15:40-60; the mass ratios of NaOH, deionized water and reducing agent in the aqueous phase W12 are 20-45:52-79.5:0.5-3; the mass ratios of chloroform, dichloromethane and rubber latex in the oil phase O1 are 23-60:30-47:10-30; the mass ratios of the aqueous phase W11, the oil phase O1 and the emulsifier E1 are 10-40:55-89:1-5; the mass ratios of the aqueous phase W12, the oil phase O1 and the emulsifier E1 are 10-45:50-89:1-5.

4. A UV-cured coating with electromagnetic shielding effect according to claim 2 or 3, characterized in that: The reducing agent is at least one of N,N-dimethyl-p-toluidine, tetramethylthiourea, and aldehyde-amine condensation products; the rubber latex is at least one of natural rubber latex, epoxidized natural rubber latex, nitrile rubber latex, and acrylate emulsion; and the emulsifier E1 is at least one of sucrose fatty acid ester, polyglycerol fatty acid ester, and polyoxyethylene castor oil.

5. The UV-curable coating with electromagnetic shielding function according to claim 2, characterized in that: The step (2) further comprises the following steps: mixing deionized water and emulsifier E2 in advance at a stirring speed of 500 to 1000 rpm / min, a temperature of 20 to 30° C., and a time of 10 to 30 min for standby use, wherein the mass ratio of deionized water to emulsifier E2 is 95-99:1-5, and is recorded as W2; the mass ratios of W11 / O1, W12 / O1, and W2 are 10-20:10-20:60-80 respectively; and the emulsifier E2 is at least one of glyceryl stearate PEG-100, Croda A165 emulsifier, ABIL CARE 85 silicone emulsifier, EG emulsifier, Prexin 721 emulsifier, and BASF A25 emulsifier.

6. The UV-curable coating with electromagnetic shielding function according to claim 5, characterized in that: The step (3) further comprises the following steps: mixing chloroform, dichloromethane, acrylate monomer and initiator in advance at a stirring speed of 500 to 1000 rpm / min, a temperature of 20 to 30°C and a time of 10 to 30 min for standby use and recording the mixture as oil phase O2, wherein the mass ratios of chloroform, dichloromethane, acrylate monomer and initiator in the oil phase O2 are 14-25:26-49:25-55:1-5 respectively; and dripping the mixed oil phase O2 into the latex particle bundle wrapping the magnetic particle Fe3O4 while stirring, wherein the material temperature of the latex particle bundle wrapping the magnetic particle Fe3O4 is 30 to 60°C during the dripping.

7. The UV-curable coating with electromagnetic shielding function according to claim 6, characterized in that: The mass ratio of the sum of the three W11 / O1, W12 / O1 and W2 to the oil phase O2 is 60-80:20-40; the acrylate monomer is at least one of styrene, acrylonitrile and methyl methacrylate; the initiator is at least one of benzoyl peroxide and isopropylbenzene hydroperoxide.

8. The UV-curable coating with electromagnetic shielding function according to claim 2, characterized in that: The cleaning in step (4) is to first use anhydrous ethanol to wash the product 1 to 2 times, and then use deionized water to wash it 3 to 4 times. The drying is to dry it at 80° C. for 2 hours.

9. The UV-curable coating with electromagnetic shielding function according to claim 1, characterized in that: The monofunctional diluent is at least one of isobornyl acrylate, glyceryl acetonide acrylate, benzyl acrylate, hydroxyethyl acrylate, and hydroxypropyl acrylate; the difunctional diluent is at least one of 1,6-hexanediol diacrylate, dipropylene glycol diacrylate, and ethoxylated bisphenol A diacrylate; the toughening resin is at least one of CN8004, CN3108, and CN704 produced by Sartomer; the photoinitiator is at least one of 1-hydroxycyclohexyl phenyl ketone, 2,4,6-trimethylbenzoyl diphenyl oxide, and benzoin dimethyl ether; the blue pigment is at least one of Runba P5040LW, BASF L7101F, and BASF 7080K.

10. A method for preparing a UV-curable coating having electromagnetic shielding effect as claimed in any one of claims 1 to 9, characterized in that: The following steps are involved: Add monofunctional diluent, difunctional diluent, photoinitiator and blue pigment in proportion by weight and stir for 1 to 2 hours at a speed of 800 to 1200 r / min until the material becomes uniform and fine. Then add homemade magnetic core-shell rubber particles and stir for 1 to 2 hours at a speed of 500 to 1000 r / min until the material becomes uniform and fine. Finally, add toughening resin and stir for 0.5 to 1 hour at a speed of 800 to 1200 r / min. During the whole process, the material temperature is controlled at 20 to 30°C. Finally, evacuate for 5 minutes to degas, discharge and seal for packaging, and the vacuum degree is ≤-0.095Mpa.

Citation Information

Cited By

  • Flexible absorbent for reducing deformation of co-curing plate and preparation method and application thereof

    CN120795420A